Stewardship and Sustainability: Islamic Legal Frameworks for Environmental Ethics and Climate Action - Asif Bashir (PT. Radja Intercontinental Publishing, 2025)
This article interrogates the juridical and ethical architecture of Islamic law as it pertains to environmental protection and the planetary climate emergency. It argues that the Qur’ānic anthropology of khilāfah (trusteeship), the cosmological notion of mīzān (equilibrium), and the prohibition of fasād fī al-arḍ (corruption upon the earth) constitute an ontological grammar for sustainable praxis. Prophetic dicta concerning frugality in water use, arboriculture, and the humane treatment of non-human creatures underscore an ethos of restraint and interspecies solidarity. Classical jurists, through the idioms of maṣlaḥah (public welfare), ḥimā reserves, and equitable water allocation, provided early normative scaffolding for ecological custodianship, while contemporary ijtihād—exemplified in eco-fatwas on pollution, deforestation, and greenhouse-gas mitigation—expands this discourse to address the unprecedented exigencies of the Anthropocene. The article further re-reads the maqāṣid al-sharīʿah, contending that the canonical objectives of preserving life, intellect, property, lineage, and religion presuppose the viability of the biosphere itself. By analysing Indonesian eco-fatwas, Islamic eco-movements, and interfaith climate alliances, the study reveals a capacious field of legal and ethical possibilities, even as it identifies deficits in policy coordination, epistemic integration, and public awareness. It concludes that an intellectually rigorous synthesis of Sharīʿah reasoning, empirical environmental science, and participatory governance can furnish Muslim societies with a distinctive, normatively grounded contribution to global sustainability discourses.